HUBUNGAN ANTARA STATUS SOSIAL EKONOMI DENGAN PERSEPSI MASYARAKAT TENTANG GANTUNG DIRI DI KECAMATAN KARANGMOJO KABUPATEN GUNUNGKIDUL YOGYAKARTA - Tiwi Sudyasih, dkk; Mamat Lukman (Universitas Aisyiyah Yogyakarta, 2015)
The Purpose of research was to determine the relationship between socioeconomic status with public perception of suicide. This research was corelation descriptive quantitative. The population in this study was district Karangmojo Gunungkidul's people age 55 to 60 years amounted to 3.091 people. The sample in this study amounted to 356 people. The technique of collecting data using questionnaires. The analysis used is regression analysis and partial correlation. The results of this research the of socioeconomic status factor made moderate category (79.78%), then the result of the public perception of suicide negative category (81.74%), more than public perception of suicide positive category (18.26%). In conclusions there was a relationship between socioeconomic status with public perceptions of suicide in Karangmojo Gunungkidul Yogyakarta.Keywords: socioeconomic status, public perception of suicide